A study on alpha-terpineol in Alzheimer's disease with the use of rodent in vivo model, restraint stress effect and in vitro Amyloid beta fibrils - Hamid-Reza Alipour; Parichehreh Yaghmaei; Shahin Ahmadian; Maryam Ghobeh; Azadeh Ebrahim-Habibi (Universidade de São Paulo, 2022)
Abstract Alzheimer's disease (AD) is a neurological disorder in which the neuronal degeneration is associated with inflammatory processes and oxidative stress. Since alpha-terpineol was shown to possess antioxidant and anti-inflammatory effects, the administration of this compound was studied on a rat model of AD. To create this model, Aβ1-42 was injected into the hippocampus of male Wistar rats. Generated AD models were divided into simple AD models and AD models in which short-term immobilization stress was added. Preventive and therapeutic (post-AD induction) effects of alpha-terpineol consumption (100 mg/Kg) were subsequently investigated in AD models, which were compared with control groups. Biochemical factors (superoxide dismutase and malondialdehyde), histological manifestations (amyloid plaques and neuron counts) and possible memory impairment (shuttle-box experiment) were investigated in all groups. For the in vitro experiment, alpha-terpineol effect was checked on Aβ1-42 fibril formation. In preventive and therapeutic modes, alpha-terpineol consumption could improve neurogenesis and long-term memory while reducing amyloid plaque counts and ameliorating biochemical factors (higher levels of superoxide dismutase and malondialdehyde and reduced levels of MDA). In vitro, shorter fibrillar structures were formed in the presence of alpha-terpineol, which indicates an anti-amyloid effect for this compound. In conclusion, alpha-terpineol significantly counteracted AD consequences.